Cost-effectiveness of generic celecoxib in knee osteoarthritis for average-risk patients: a model-based evaluation. Issue 5 (May 2018) - Losina, E.; Usiskin, I.M.; Smith, S.R.; Sullivan, J.K.; Smith, K.C.; Hunter, D.J.; Messier, S.P.; Paltiel, A.D.; Katz, J.N.
Summary: Objective: The cost-effectiveness of the recently-introduced generic celecoxib in knee OA has not been examined. Method: We used the Osteoarthritis Policy (OAPol) Model, a validated computer simulation of knee OA, to evaluate long-term clinical outcomes, costs, and cost-effectiveness of generic celecoxib in persons with knee OA. We examined eight treatment strategies consisting of generic celecoxib, over-the-counter (OTC) naproxen, or prescription naproxen, with or without prescription or OTC proton-pump-inhibitors (PPIs) to reduce gastrointestinal (GI) toxicity. In the base case, we assumed that annual cost was $130 for OTC naproxen, $360 for prescription naproxen, and $880 for generic celecoxib. We considered a willingness-to-pay threshold of $100, 000 per quality-adjusted life year (QALY) and discounted costs and benefits at 3% annually. In sensitivity analyses we varied celecoxib toxicity, discontinuation, cost, and pain level. Results: In the base case analysis of the high pain cohort (WOMAC 50), celecoxib had an incremental cost-effectiveness ratio (ICER) of $284, 630/QALY compared with OTC naproxen. Only under highly favorable cost, toxicity, and discontinuation assumptions (e.g., annual cost below $360, combined with a reduction in the cardiovascular (CV) event rates below baseline values) was celecoxib likely to be cost-effective. Celecoxib might also be cost-effective at an annual cost of $600 if CV toxicity were eliminated completely. In subjects with moderate pain (WOMAC 30), at the base case CV event rate of 0.2%, generic celecoxib was only cost-effective at the lowest plausible cost ($190). Conclusion: In knee OA patients with no comorbidities, generic celecoxib is not cost-effective at its current price.